Overview of Biologic Agents Used in Skin and Soft Tissue Reconstruction - Parham, Matthew J.; Grush, Andrew E.; Smerica, Abel; Wen, Y. Edward; Depani, Monal; Ferry, Andrew M.; Jones, Lloyd M.; Thornton, James F. (Seminars in Plastic Surgery, 2022)
Wound healing is a highly complex process mediated by cellular interactions at the microscopic level. Increased understanding of wound healing physiology has served as the foundation for translational research to develop biologic wound care technologies that have profoundly affected patient care. As the reader will see throughout this series in Seminars in Plastic Surgery, biologic wound technologies have broad applications and have greatly impacted the reconstructive ladder. Despite their frequent use, many surgeons lack familiarity with the myriad of products available on the market along with each product's relative advantages and shortcomings. This overview will discuss the classification of biologic wound agents used to reconstruct defects of the skin and soft tissue along with the advantages and disadvantages associated with their use.
Keywords: biologics; biocompatible materials; acellular dermis; wounds and injuries; plastic surgery